Update on dermatophytosis in Mashhad, Northeastern Iran, emergence of infection with Trichophyton persicum - Fatemeh Afsharzadeh; Hossein Zarrinfar; Abdolmajid Fata; Mohammad Javad Najafzadeh (Wolters Kluwer Medknow Publications, 2022)
Background: Dermatophytosis is a common global superficial mycosis caused by a group of keratinophilic moulds known as dermatophytes that invade the skin and keratinized tissues such as hair and nails of humans and animals. This study takes identification of a collection of clinical dermatophyte isolates by using partial sequencing of translation elongation factor-1α (Tef-1α) gene aiming both to update the epidemiological status of dermatophytosis in Mashhad, Northeastern Iran and to corroborate the efficacy of Tef-1α for species-level identification of dermatophytes. Method: The demographic data related to 87 culture-positive dermatophytes isolated from patients clinically suspected to have dermatophytosis were collected. The dermatophyte isolates were subjected to a partial polymerase chain reaction (PCR)-sequencing of Tef-1α gene by using specific pan-dermatophyte primers. The data were analysed by SeqMan software, the sequences were compared and aligned with the GenBank database and the isolates were identified. Results: Identification based on Tef-1α partial sequence was successful for all isolates. The identified dermatophyte isolates in decreasing order were as Trichophyton interdigitale 19 (22%), T. tonsurans 19 (22%), T. mentagrophytes 13 (15%), T. persicum 10 (11.5%), Epidermophyton floccosum 9 (10.3%), Microsporum canis 7 (8%), T. rubrum 5 (5.7%), T. violaceum 2 (2.2%), Nannizzia fulva 2 (2.2%) and N. persicolor 1 (1.1%). The isolates have been associated with clinical forms of tinea corporis (n = 38; 43.7%), tinea faciei (n = 13; 15%), tinea cruris (n = 12; 13.9%), tinea manuum (n = 7; 8%), tinea unguium (n = 7; 8%), tinea capitis (n = 7; 8%) and tinea pedis (n = 3; 3.4%). Conclusion: Dermatophytosis has yet remained a public health problem in Northeastern Iran, and infection with new and less frequent species, e.g., T. persicum, N. fulva and N. persicolor have emerged. The Tef-1α gene partial sequencing reconfirmed the resolution power of this locus for the determination of species boundaries in dermatophytes.